Dampak Media Sosial Tiktok terhadap Akhlak Siswa di MA Baiturrahim Jayapura - Atikah Ainun Mardiyah; Muhamad Thoif; Izzatul Laili; Mirza A’yunil Laili (Pusat Riset dan Inovasi Nasional, 2024)
The development of social media, especially the TikTok application, has various influences on adolescent behavior, including the aspect of student morality in the school environment. This study aims to: (1) determine the description of student morality at MA Baiturrahim Jayapura, and (2) analyze the impact of TikTok social media use on student morality at MA Baiturrahim Jayapura. This study uses a qualitative approach with a field research type. Data sources in this study consist of primary data obtained from informants through interviews and observations, as well as secondary data obtained from books, documents, and relevant research results. The determination of informants was carried out using purposive sampling and snowball sampling techniques. Data collection techniques were carried out through observation, interviews, and documentation. Data validity was tested through credibility, transferability, dependability, and confirmability tests. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that student morality at MA Baiturrahim Jayapura has a variety of behaviors. Some students still show a lack of discipline towards school rules, such as underestimating the applicable rules, while others continue to comply with the established rules. Research findings also indicate that TikTok use influences student behavior, particularly in the way they speak, which is influenced by the content they consume on social media. Lack of supervision and enforcement from schools also contributes to this behavior. Therefore, student awareness of the importance of using social media wisely, along with the active role of teachers and schools in providing guidance, is needed to ensure that social media use does not negatively impact students' moral development.